Accelerating Methane Reductions in Rice Production Systems Through Market-Based Mechanisms: Insight from Farmer Surveys and Choice Experiments in Thailand - Villanueva, Donald B.; Labios, Jade Ruth; Pajadan, Karen M.; Revicoy, Riela Rose R.; Malana, Xyla Mae L.; De Castro, Allenie M.; Napasintuwong, O.; Duangbootsee, U.; Punjatewakupt, P.; Mirzabaev, Alisher (International Rice Research Institute, 2025)
Thailand’s rice industry plays a vital role in ensuring food security and supporting farmer incomes, yet it is also a significant source of methane emissions. To better understand farmers’ views and uptake of low-emission practices, this study surveyed 401 rice farmers across five key irrigated rice-growing provinces: Suphan Buri, Ayutthaya, Chai Nat, Kalasin, and Phitsanulok. Using choice experiments, the research examined farmers’ willingness to accept payments for adopting climatesmart agriculture (CSA) practices - including Alternate Wetting and Drying (AWD), Direct-Seeded Rice (DSR), and Improved Rice Straw Management (RSM) - within potential carbon market schemes. The results offer guidance for shaping CSA policies, designing strategies for carbon market participation, and directing investments to expand sustainable rice production.